The interrelationships of sustainable livelihood capital assets deprivations and asset based social policy interventions: The case of Addis Ababa informal settlement areas, Ethiopia - Gizachew Berhanu; Solomon Mulugeta Woldemikael; Ephrem Gebremariam Beyene (Research in Globalization, 2022)
The purpose of the research is to analyze the pattern of interrelationships in deprivations of sustainable livelihood capital assets, sub-groups deprivation variations in light of the theoretical and empirical frameworks, and suggest recommendations for Asset Based Social policy (ABS). The research reviews the approaches of informal settlement interventions vis-a-vise livelihood capital assets, how livelihood capital assets deprivations affect each other, the relationships of assets and functioning of capability, and the institution role on access and control of assets by vulnerable sub-groups. The case study area was from two informal settlements of Addis Ketema sub-city Wereda 07 (the inner-city slum) and kolfe keranyo sub-city Wereda 03 (peri-urban). The research applied an explanatory mixed-method sequential design consisting of quantitative research based on a house-to-house random sampling survey, followed by the qualitative method of individual case study and key-informants interview. The research refined strategic issues/ indicators that require ABS interventions from the many aspects of deprivations relationships and argued in line with the theoretical and empirical frameworks. The research implicated strengthening institutions to make livelihood capital assets closer to vulnerable sub-groups, especially in peri-urban, empowering community associations bargain for poor rights, reinforce capability functioning for livelihood capital asset accumulation. ABS is crucial for addressing the strategic issue of livelihood capital assets deprivations, tackling institutional and legal constraints, effective functioning of assets and capability, address risk, safety, and vulnerability in informal settlements. The ABS policy improves the wellbeing of poor and vulnerable sub-groups through asset accession, asset valorization, and asset consolidation.
Keywords: 330; Livelihood capital assets deprivations; Asset-Based Social Policy; Sub-groups; Capability; Institution